2018 IEEE Symposium on Security and Privacy (SP) 2018
DOI: 10.1109/sp.2018.00050
|View full text |Cite
|
Sign up to set email alerts
|

Blue Note: How Intentional Acoustic Interference Damages Availability and Integrity in Hard Disk Drives and Operating Systems

Abstract: Intentional acoustic interference causes unusual errors in the mechanics of magnetic hard disk drives in desktop and laptop computers, leading to damage to integrity and availability in both hardware and software such as file system corruption and operating system reboots. An adversary without any special purpose equipment can co-opt built-in speakers or nearby emitters to cause persistent errors. Our work traces the deeper causality of these risks from the physics of materials to the I/O request stack in oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 22 publications
0
41
0
Order By: Relevance
“…The term (sensor) spoofing [8], [9], [14], [43] was also Injection [5], [13], [35], [38], [41]- [44] Intentional Interference [5], [10], [12], [36], [38], [40], [42], [49] Non-Linearity [11], [54], [55], [68] Spoofing [8], [9], [14], [43] Other (See Text) [7], [53], [67] avoided for similar reasons: it has an overloaded meaning in authentication contexts and with in-band signal injection attacks [6], [52]. Moreover, it does not capture the physical aspect of injections, and does not accurately describe coarsegrained attacks which lead to saturation of a sensor.…”
Section: Choice Of Terminologymentioning
confidence: 99%
See 4 more Smart Citations
“…The term (sensor) spoofing [8], [9], [14], [43] was also Injection [5], [13], [35], [38], [41]- [44] Intentional Interference [5], [10], [12], [36], [38], [40], [42], [49] Non-Linearity [11], [54], [55], [68] Spoofing [8], [9], [14], [43] Other (See Text) [7], [53], [67] avoided for similar reasons: it has an overloaded meaning in authentication contexts and with in-band signal injection attacks [6], [52]. Moreover, it does not capture the physical aspect of injections, and does not accurately describe coarsegrained attacks which lead to saturation of a sensor.…”
Section: Choice Of Terminologymentioning
confidence: 99%
“…Although Shahrad et al primarily focused on the effect of the angle of transmission [53], research conducted in parallel more precisely pinpointed the root cause of the issue using Finite Element Analysis [12]. Specifically, it was shown that (audible) acoustic waves "can displace a read/write head or disk platter outside of operational bounds, inducing throughput loss", even though the displacement is of only a few nanometers [12].…”
Section: Acoustic Emanationsmentioning
confidence: 99%
See 3 more Smart Citations